PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEAD TOGETHER BERBANTUAN MEDIA VIDEO ANIMASI UNTUK MENINGKATKAN PARTISIPASI PESERTA DIDIK DALAM PENDIDIKAN PANCASILA DI KELAS IV SD NEGERI 018 MANDING KABUPATEN POEWALI MANDAR - Tuken, Ritha; Usman, Usman; Alimin, Mutmainnah Deila (JIKAP PGSD: Jurnal Ilmiah Ilmu Kependidikan, 2025)
Abstract: The research is a Classroom Action Research with qualitative research.  The purpose of this study was to determine how the application of cooperative learning model type Numbered Head Together assisted by animated video media can improve the quality of the learning process and the participation of students in class IV SD Negeri 018 Manding. The research subjects consisted of 1 teacher and 26 fourth grade students of SD Negeri 018 Manding. Data were colected through observation and documentation techniques. The research method is data condensation, data presentation, and conclusion drawing. The results of the research in cycle 1 teacher activity was in the sufficient category (C) with a percentage of 75% and increased in cycle 2 to a good category (B) with a percentage of 91.66%. Student activity in cycle 1 was in the sufficient category (C) with a percentage of 69%, increasing in cycle 2 to a good category (B) with a percentage of 89%. Learner participation in cycle 1 reached sufficient qualification (C) with a percentage of 61%. In cycle 2, learner participation reached good qualification (B) with a percentage of 80%. Based on these results, it can be concluded that the application of the Numbered Head Together learning model is effective in improving the quality of the learning process and the participation of fourth grade students of SD Negeri018 Manding.